Question
upstudy study bank question image url

Find the derivative of the function \( F(x)=\left(\frac{5 x-3}{4-7 x}\right)^{6} \)

Ask by Young Jimenez. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of \( F(x) = \left(\frac{5x - 3}{4 - 7x}\right)^6 \) is \( F'(x) = -6 \cdot \frac{(5x - 3)^5}{(4 - 7x)^7} \).

Solution

We are given the function   F(x) = ((5x - 3)/(4 - 7x))⁶. To find F'(x), we can use the chain rule. Let   u(x) = (5x - 3)/(4 - 7x). Then F(x) = [u(x)]⁶, so by the chain rule:   F'(x) = 6[u(x)]⁵ · u'(x). Now, we need the derivative u'(x). Since u(x) is a quotient, we'll use the quotient rule. The quotient rule states that if u(x) = N(x) / D(x), then   u'(x) = [N'(x)D(x) - N(x)D'(x)] / [D(x)]². For our function, identify:   N(x) = 5x - 3  with  N'(x) = 5,   D(x) = 4 - 7x  with  D'(x) = -7. Plug these into the quotient rule:   u'(x) = [5(4 - 7x) - (5x - 3)(-7)] / (4 - 7x)². Simplify the numerator:   5(4 - 7x) = 20 - 35x,   (5x - 3)(-7) = -35x + 21. Thus:   Numerator = (20 - 35x) - (-35x + 21) = 20 - 35x + 35x - 21 = 20 - 21 = -1. So, u'(x) = -1 / (4 - 7x)². Returning to our original derivative:   F'(x) = 6[u(x)]⁵ · u'(x) = 6[(5x - 3)/(4 - 7x)]⁵ · (-1/(4 - 7x)²). This simplifies to:   F'(x) = -6 (5x - 3)⁵ / [(4 - 7x)⁵ · (4 - 7x)²]          = -6 (5x - 3)⁵ / (4 - 7x)⁷. So the derivative of F(x) is:   F'(x) = -6 (5x - 3)⁵ / (4 - 7x)⁷.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To find the derivative of the function \( F(x)=\left(\frac{5 x-3}{4-7 x}\right)^{6} \), we will use the chain rule and the quotient rule. Firstly, let \( u = \frac{5x - 3}{4 - 7x} \). Then, we can rewrite \( F(x) = u^6 \). Now apply the chain rule: \[ F'(x) = 6u^5 \cdot u' \] Next, we need to find \( u' \) using the quotient rule: \[ u' = \frac{(5)(4 - 7x) - (5x - 3)(-7)}{(4 - 7x)^2} \] Calculating the numerator: \[ u' = \frac{20 - 35x + 35x - 21}{(4 - 7x)^2} = \frac{20 - 21}{(4 - 7x)^2} = \frac{-1}{(4 - 7x)^2} \] Now, substitute \( u \) and \( u' \) back into the derivative of \( F \): \[ F'(x) = 6\left(\frac{5x - 3}{4 - 7x}\right)^5 \cdot \left(\frac{-1}{(4 - 7x)^2}\right) \] We can simplify this to: \[ F'(x) = \frac{-6(5x - 3)^5}{(4 - 7x)^7} \] Thus, the derivative of the function \( F(x) \) is: \[ F'(x) = \frac{-6(5x - 3)^5}{(4 - 7x)^7} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy